Novel alkoxyamines for the successful controlled polymerization of styrene and methacrylates. Issue 10 (20th February 2017) - Simula, Alexandre; Aguirre, Miren; Ballard, Nicholas; Veloso, Antonio; Leiza, José R.; van Es, Steven; Asua, José M.
Abstract : The design of alkoxyamine/nitroxide species capable of mediating the polymerization of both styrene and methacrylic monomers has been notoriously difficult. Abstract : The design of alkoxyamine/nitroxide species capable of mediating the polymerization of both styrene and methacrylic monomers has been notoriously difficult. Herein, the nitroxide-mediated polymerization of styrene using a series of readily obtained alkoxyamines that were recently shown to control the polymerization of methyl methacrylate is presented. The robustness of the system is tested towards different temperatures and molecular weights. The influence of the substitution pattern in the nitroxide adducts on the polymerization of styrene is monitored through kinetic analyses. An alkoxyamine that can successfully mediate the homopolymerization of styrene and methyl methacrylate is presented. This alkoxyamine is subsequently utilized for the synthesis of PMMA- b -PS and PS- b -PBMA copolymers.